Effect of bupropion-SR on REM sleep: relationship to antidepressant response - Geoffrey Ott; Uma Rao; Innocencia Nuccio; Keh-Ming Lin; Russell Poland (Psychopharmacology, 2002)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)

IGF-I of Orange Spotted Grouper Epinephelus Coioides: cDNA Cloning, Sequencing and Expression in Escherichia Coli - F.T. Shi; W.S. Li; C.H. Bai; H.R. Lin (Fish Physiology and Biochemistry, 2002)

Effect of rice-glycerol complex medium on the production of lovastatin byMonascus ruber - Y. N. Chang; Y. C. Lin; C. C. Lee; B. L. Liu; Y. M. Tzeng (Folia Microbiologica, 2002)

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Digestion Methods for Total Heavy Metals in Sediments and Soils - Zeng-Yei Hseu; Zueng-Sang Chen; Chen-Chi Tsai; Chun-Chih Tsui; Shuang-Fu Cheng; Chyan-Lan Liu; Haw-Tarn Lin (Water, Air, & Soil Pollution, 2002)

The Use of in Vitro Metabolic Stability for Rapid Selection of Compounds in Early Discovery Based on Their Expected Hepatic Extraction Ratios - Yau Yi Lau; Gopal Krishna; Nathan P. Yumibe; Diane E. Grotz; Elpida Sapidou; Laura Norton; Inhou Chu; Cliff Chen; A. D. Soares; Chin-Chung Lin (Pharmaceutical Research, 2002)

Nitric oxide-containing pyramidal neurons of the subiculum innervate the CA1 area - László Seress; Hajnalka ÁbrahÁm; Hong Lin; Susan Totterdell (Experimental Brain Research, 2002)

Deregulated activation of matriptase in breast cancer cells - Christelle M. Benaud; Michael Oberst; Robert B. Dickson; Chen-Yong Lin (Clinical & Experimental Metastasis, 2002)

Oxidation of elemental sulfur in paddy soils as influenced by flooded condition and plant growth in pot experiment - Wei Zhou; Min Wan; Ping He; Shutian Li; Bao Lin (Biology and Fertility of Soils, 2002)

Fractionation of protein adducts in rats and mice dosed with [ 14 C]pentachlorophenol - Chin-Hsiang Tsai; Po-Hsiung Lin; Suramya Waidyanatha; Stephen Rappaport (Archives of Toxicology, 2002)

Inhibitory effect of berberine on tert -butyl hydroperoxide-induced oxidative damage in rat liver - Jin-Ming Hwang; Chau-Jong Wang; Feu-Pi Chou; Tsui-Hwa Tseng; Yih-Shou Hsieh; Wea-Lung Lin; Chia-Yih Chu (Archives of Toxicology, 2002)

Biological Monitoring of Environment Exposure to Safrole and the Taiwanese Betel Quid Chewing - M. J. W. Chang; C. Y. Ko; R. F. Lin; L. L. Hsieh (Archives of Environmental Contamination and Toxicology, 2002)

Spatial pattern of chloroplast DNA variation of Cyclobalanopsis glauca in Taiwan and East Asia - Sophie S. F. Huang; Shih‐Ying Hwang; Tsan‐Piao Lin (Molecular Ecology, 2002)
This study examined the spatial pattern of chloroplast DNA (cpDNA) variation in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. (Fagaceae) in 140 trees from Taiwan (25 populations), Japan (three), Ryukyus (two), Hong Kong (one) and Mainland China (one). By sequencing three cpDNA intergenic spacer fragments using universal primers ( trn T ‐trn L, trn V ‐trn M, including the trn V intron, and pet G ‐trn P), we found a total of 1980 bp and 15 polymorphic sites. Among them, 12 sites were caused by point mutation, and three resulted from insertion. This gives rise to a total of 13 cpDNA haplotypes. The level of differentiation among the populations studied is relatively high ( G ST = 0.612). Two ancestral haplotypes (A and B) are distributed widely in East Asia. Interestingly, all the derived cpDNA variations are found only in Taiwan but not in other areas. The Central Mountain Ridge (CMR) of Taiwan creates an unsurpassed barrier to the east–west gene flow of C. glauca . Among the populations on the west of CMR, only three separated populations, Yangmingshan, Wushe and Chinshuiying, have high haplotype diversity, each consisting of sister haplotypes all mutated from the same ancestral haplotype. Thus, they have probably originated from de novo mutation after the last glaciation. This inference agrees with the observation that no spatial autocorrelation existed on the west side. Two unrelated dominant lineages on the east of the CMR (haplotypes D and F) showed significant spatial genetic structure. Estimate of N ST – G ST was –0.090 and differed significantly from zero. Thus at the local scale, the phylogeographical component of the genetic structure is significant on the east of the CMR. Accompanied by published palynological records of the last glaciation, this study suggests the possibility that these two types were colonized northward from the southeastern part of Taiwan. ‘Star‐like’ genealogy is characterized, with all the haplotypes coalescing rapidly and as a general outcome of population expansion ( Page & Holmes 1998 ). A neutrality test also suggested a demographic expansion recovered from a bottleneck. We therefore inferred that the southeastern part of Taiwan might be a potential refugium for C. glauca .

Soil Vulnerability and Sensitivity to Acid Deposition in China - Fulu Tao; Yousay Hayashi; Erda Lin (Water, Air, & Soil Pollution, 2002)

The Arterial Supply to the Eye of the Bactrian Camel (Camelus bactrianus) - Jian-Lin Wang (Veterinary Research Communications, 2002)

Spectral analysis of water level fluctuations in aquifers - D. C.-F. Shih; G.-F. Lin (Stochastic Environmental Research and Risk Assessment, 2002)

Preprophase band loses its function as a cytokinetic apparatus in mitosis of neck canal mother cell - Qun He; Rui-Lin You; Sodmergen Not Available; Wen-Mei Bao (Protoplasma, 2002)

Specific detection ofPythium aphanidermatum from hydroponic nutrient solution by booster PCR with DNA primers developed from mitochondrial DNA - P. H. Wang; L. M. Boo; Y. S. Lin; Y. Yeh (Phytoparasitica, 2002)

Nitric oxide is not involved in the endotoxemia-induced alterations in Ca 2+ and ryanodine responses in mouse diaphragms - Shing-Hwa Liu; Jiun-Li Lai; Rong-Sen Yang; Shoei-Yn Lin-Shiau (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

An alternative interpretation of lower mantle mineral associations in diamonds - Lin-gun Liu (Contributions to Mineralogy and Petrology, 2002)

Dietary supplementation with isolated soy protein reduces metastasis of mammary carcinoma cells in mice - Lin Yan; Donghua Li; John A. Yee (Clinical & Experimental Metastasis, 2002)

The Chemical Transformations of Chromium in Natural Waters – A Model Study - Che-Jen Lin (Water, Air, & Soil Pollution, 2002)

Suppression subtractive hybridization cloning of cDNAs of differentially expressed genes in dovetree (Davidia involucrata) bracts - Yun-Xiang Li; Li Chen; Lin Juan; Yufeng Li; Fang Chen (Plant Molecular Biology Reporter, 2002)

Intra- and Interfamily Relationships of Vespertilionidae Inferred by Various Molecular Markers Including SINE Insertion Data - Kuniko Kawai; Masato Nikaido; Masashi Harada; Sumiko Matsumura; Liang-Kong Lin; Yi Wu; Masami Hasegawa; Norihiro Okada (Journal of Molecular Evolution, 2002)

Characteristics of Environmental Geochemistry in the Arseniasis Area of the Inner Mongolia of China - Nian-Feng Lin; Jie Tang; Jian-Min Bian (Environmental Geochemistry and Health, 2002)

Spatial-temporal variation of heavy metal elements content in covering soil of reclamation area in fushun coal mine - Jun-bao Yu; Jing-shuang Liu; Jin-da Wang; Zhong-gen Li; Xue-lin Zhang (Chinese Geographical Science, 2002)

The strategies of integrating spatial data analysis and GIS - Zheng-yuan Mao; Lin Li (Chinese Geographical Science, 2002)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.

Yield Surface of Mu-San Sandstone by Hollow Cylinder Tests - D.-H. Lee; C. H. Juang; H.-M. Lin (Rock Mechanics and Rock Engineering, 2002)

Sapling growth and survivorship as a function of light in a mesic forest of southeast Texas, USA - Jie Lin; Paul A. Harcombe; Mark R. Fulton; Rosine W. Hall (Oecologia, 2002)

Cloning and sequencing of the phycocyanin gene from Spirulina maxima and its evolutionary analysis - Ping Yu; Jian-Rong Li; Pei-Lin Cen (Journal of Applied Phycology, 2002)

Phenotypic polymorphism of CYP2A6 activity in a Chinese population - Ping Xu; Song-Lin Huang; Rong-Hua Zhu; Xing-Mei Han; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Animal-related occupations and the risk of leukemia, myeloma, and non-Hodgkin's lymphoma in Canada - Lin Fritschi; Kenneth C. Johnson; Erich V. Kliewer; Rick Fry (Cancer Causes & Control, 2002)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Deletion analysis of the C-terminal region of the α-amylase of Bacillus sp. strain TS-23 - Huei-Fen Lo; Long-Liu Lin; Wen-Ying Chiang; Meng-Chun Chie; Wen-Hwei Hsu; Chen-Tien Chang (Archives of Microbiology, 2002)

Adsorption of Copper in the Different Sorbent/Water Ratios of Soil Systems - T. W. Chang; M. K. Wang; C. Lin (Water, Air, & Soil Pollution, 2002)

Effect of Water Extract of Compost on the Adsorption of Arsenate by Two Calcareous Soils - Haw-Tarn Lin; M. C. Wang; Gwo-Chen Li (Water, Air, & Soil Pollution, 2002)

Downregulation of PTEN/MMAC/TEP1 expression in human prostate cancer cell line DU145 by growth stimuli - Dhundy R. Bastola; Gurcharan S. Pahwa; Ming-Fong Lin; Pi-Wan Cheng (Molecular and Cellular Biochemistry, 2002)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Lack of growth hormone-releasing peptide-6 action on in vivo and in vitro growth hormone secretion in sexually immature grass carp (Ctenopharyngodon idellus) - Dong Xiao; Anderson O.L. Wong; Hao-Ran Lin (Fish Physiology and Biochemistry, 2002)

The cost of habitat selection in prairie voles: an empirical assessment using isodar analysis - Yu-Teh K. Lin; George O. Batzli (Evolutionary Ecology, 2002)

Germplasm improvement for preharvest sprouting resistance in Chinese white-grained wheat: An overview of the current strategy - Shi-He Xiao; Xiu-Ying Zhang; Chang-Sheng Yan; Hai Lin (Euphytica, 2002)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

A personal perspective on the further reform of the advances in atmospheric sciences - Da-Lin Zhang (Advances in Atmospheric Sciences, 2002)

A comparative analysis of computational stability for linear and non-linear evolution equations - Lin Wantao; Ji Zhongzhen; Wang Bin (Advances in Atmospheric Sciences, 2002)

Evolution of DNA Polymerase Families: Evidences for Multiple Gene Exchange Between Cellular and Viral Proteins - Jonathan Filée; Patrick Forterre; Tang Sen-Lin; Jacqueline Laurent (Journal of Molecular Evolution, 2002)

Allelic and locus heterogeneity in autosomal recessive gelatinous drop-like corneal dystrophy - Zhaoxia Ren; Pei-Yu Lin; Gordon K. Klintworth; Fumino Iwata; Francis L. Munier; Daniel F. Schorderet; Leila El Matri; Veena Theendakara; Surendra Basti; Madhukar Reddy; Fielding J. Hejtmancik (Human Genetics, 2002)

Organization and Phylogenetic Analysis of κ-Bungarotoxin Genes from Bungarus Multicinctus (Taiwan Banded Krait) - Long-sen Chang; Charling Chung; Jordge Lin; Enjong Hong (Genetica, 2002)

Pharmacokinetic comparison of beclomethasone dipropionate extrafine aerosol from two inhaler devices in children with asthma - Lester I. Harrison; Sarala Kurup; Lin-Zhi Chen; Bruce P. Ekholm; Timothy G. Wighton; Gail G. Shapiro (European Journal of Clinical Pharmacology, 2002)

Cloning and Regulation of the Promoter of Pseudorabies Virus (TNL Strain) Glycoprotein E Gene - Yuan-Yen Chang; Min-Liang Wong; Hui-Wen Lin; Tien-Jye Chang (Virus Genes, 2002)

Temporal and spatial expression of biologically active human factor VIII in the milk of transgenic mice driven by mammary-specific bovine α-lactalbumin regulation sequences - Chuan-Mu Chen; Chih-Hong Wang; Shinn-Chih Wu; Chih-Cheng Lin; Shwu-Hwa Lin; Winston T.K. Cheng (Transgenic Research, 2002)

Spatial correlation analysis of crop yield in the middle and west of Jilin Province - Lin-yi Li; Zhao-li Liu; Chun-lin Li; En-pu Wan (Chinese Geographical Science, 2002)

Challenges and problems: China’s urban governance - Hong Wang; Chao-lin Gu (Chinese Geographical Science, 2002)

The evaluation and analysis of the tourism resources in Jilin Province - Tao-fang Yu; Chao-lin Gu; Hong Wang; Xue-jun Duan; Xiao-feng Yi (Chinese Geographical Science, 2002)

Wogonin and fisetin induction of apoptosis through activation of caspase 3 cascade and alternative expression of p21 protein in hepatocellular carcinoma cells SK-HEP-1 - Yen-Chou Chen; Shing-Chuan Shen; Woan-Rouh Lee; Hui-Yi Lin; Ching-Huai Ko; Chun-Ming Shih; Ling-Ling Yang (Archives of Toxicology, 2002)

Stratification and seasonal stability of diverse bacterial communities in a Pinus merkusii (pine) forest soil in central Java, Indonesia - Agna S. Krave; Bin Lin; Martin Braster; Anniet M. Laverman; Nico M. van Straalen; Wilfred F. M. Röling; Henk W. van Verseveld (Environmental Microbiology, 2002)
Summary In Java, Indonesia, many nutrient‐poor soils are intensively reforested with Pinus merkusii (pine). Information on nutrient cycles and microorganisms involved in these cycles will benefit the management of these important forests. Here, seasonal effects on the stratification of bacterial community structure in the soil profile of a tropical pine forest are described, and differences in bacterial communities are related to chemical and physical soil parameters. Culture‐independent community profiles of litter, fragmented litter and mineral soil layers were made by denaturing gradient gel electrophoresis (DGGE) of 16S rDNA‐specific polymerase chain reaction (PCR) fragments. The community profiles of the different soil layers clustered separately, correlating with significant differences in organic matter content between the three layers. The bacterial communities appeared to be stable during the wet season of 1998. The drought in 1997, caused by the El Niño climatic effect, did not influence the bacterial communities in fragmentation and mineral soil, although moisture content and other soil parameters were markedly lower than in the wet season. However, communities in litter were influenced by drought. In the litter layer, the moisture content was significantly lower than in the fragmentation and mineral layers during the dry season. A clone library was made from a litter sample taken during the wet season. Partial sequencing of 74 clones and linking the DGGE banding positions of these clones to bands in the DGGE profile of the sample from which the clone library was derived showed considerable bacterial diversity. Alpha‐proteobacteria (40.5% of the clones, of which 57% belonged to the Rhizobium–Agrobacterium group) and high‐G+C content, Gram‐positive bacteria (36.5%) dominated the clone library.

Mapping quantitative trait loci controlling seed longevity in rice (Oryza sativa L.) - K. Miura; S. Lin; M. Yano; T. Nagamine (Theoretical and Applied Genetics, 2002)

Identification of QTLs for early blight (Alternaria solani) resistance in tomato using backcross populations of a Lycopersicon esculentum × L. hirsutum cross - M. Foolad; L. Zhang; A. A. Khan; D. Niño-Liu; G. Lin (Theoretical and Applied Genetics, 2002)

Some recent advances in the theory of random vibration - Lin Y. (The Science of Nature, 2002)

Phospholipase C interacts with Sgd1p and is required for expression of GPD1 and osmoresistance in Saccharomyces cerevisiae - H. Lin; P. Nguyen; A. Vancura (Molecular Genetics and Genomics, 2002)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Insights into bactericidal action of surface-attached poly(vinyl-N-hexylpyridinium) chains - Jian Lin; Joerg C. Tiller; Sang Beom Lee; Kim Lewis; Alexander M. Klibanov (Biotechnology Letters, 2002)

Lipase-catalyzed glycerolysis of an oil rich in eicosapentaenoic acid residues - Carlos Torres; Betty Lin; Charles G. Hill (Biotechnology Letters, 2002)

Developmental roles of heparan sulfate proteoglycans in Drosophila - Xinhua Lin; Norbert Perrimon (Glycoconjugate Journal, 2002)

The Pathway of Bone Fluid Flow as Defined by In Vivo Intramedullary Pressure and Streaming Potential Measurements - Yi-Xian Qin; Wei Lin; Clinton Rubin (Annals of Biomedical Engineering, 2002)

Leaf respiration is differentially affected by leaf vs. stand‐level night‐time warming - Kevin L. Griffin; Matthew Turnbull; Ramesh Murthy; Guanghui Lin; John Adams; Blake Farnsworth; Tilak Mahato; Guerric Bazin; Mark Potasnak; Joe A. Berry (Global Change Biology, 2002)
Plant respiration is an important physiological process in the global carbon cycle serving as a major carbon flux from the biosphere to the atmosphere. Respiration is sensitive to temperature providing a link between environmental variability, climate change and the global carbon cycle. We measured leaf respiration in Populus deltoides after manipulating the air temperature surrounding part of a single leaf, and compared this to the temperature response of the same leaves after manipulating the temperature of the stand. The short‐term temperature response of respiration (Q 10 – change in the respiration rate with a 10 °C increase in leaf temperature) was 1.7 when the leaf temperature was manipulated, but 2.1 when the stand‐level temperature was changed. As a result, total night‐time carbon release during the five‐day experiment was 21% lower when using the Q 10 estimates from the tradition leaf manipulation compared to the stand‐level manipulation. We conclude that the temperature response of leaf respiration is related to whole plant carbon and energy demands, and that appropriate experimental procedures are required in examining respiratory CO 2 release under variable temperature conditions.

Genetic dissection of a genomic region for a quantitative trait locus, Hd3, into two loci, Hd3a and Hd3b, controlling heading date in rice - L. Monna; H. Lin; S. Kojima; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2002)

CYP2C19 genotype and S-mephenytoin 4′-hydroxylation phenotype in a Chinese Dai population - Nan He; Feng-Xiang Yan; Song-Lin Huang; Wei Wang; Zhou-Sheng Xiao; Zhao-Qian Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Allozyme variation and conservation genetics of common wild rice (Oryza rufipogon Griff.) in Yunnan, China - Lizhi Gao; Song Ge; Deyuan Hong; Rushun Lin; Guoda Tao; Zaifu Xu (Euphytica, 2002)

A prospective cohort study of cigarette smoking and pancreatic cancer in Japan - Yingsong Lin; Akiko Tamakoshi; Takashi Kawamura; Yutaka Inaba; Shogo Kikuchi; Yutaka Motohashi; Michiko Kurosawa; Yoshiyuki Ohno (Cancer Causes & Control, 2002)

Raman spectra of hydrous γ -Mg 2 SiO 4 at various pressures and temperatures - L. Liu; C.-C. Lin; T. P. Mernagh; T. Inoue (Physics and Chemistry of Minerals, 2002)

The paleogeographic implications of loess mounds: Laizhou Bay plain - Zhang Zu-lu; Liu En-feng; Nie Xiao-hong; Wang Lin (Journal of Geographical Sciences, 2002)

Biodiversity and conservation in the Tibetan Plateau - Zhang Bai-ping; Chen Xiao-dong; Li Bao-lin; Yao Yong-hui (Journal of Geographical Sciences, 2002)

Regional carrying capacity: case studies of Bohai Rim area - Yu Dan-lin; Mao Han-ying (Journal of Geographical Sciences, 2002)

Molecular Cloning and Sequence Analysis of the cDNAs for Pituitary Glycoprotein Hormone α Subunits from Two Species of Synbranchiformes, Monopterus albus and Ophisternon bengalense - Yu-San Han; John Yuh-Lin Yu (Fish Physiology and Biochemistry, 2002)

Mapping Soil Lead and Remediation Needs in Contaminated Soils - Chi-Wen Lin (Environmental Geochemistry and Health, 2002)

Optimization of glycerol feeding for clavulanic acid production by Streptomyces clavuligerus with glycerol feeding - Kuo-Cheng Chen; Yun-Huin Lin; Cheng-Min Tsai; Chen-Hao Hsieh; Jer-Yiing Houng (Biotechnology Letters, 2002)

Evaluation of Saccharomyces cerevisiae grown in a multistage chemostat environment under increasing levels of glucose - Yen-Han Lin; D.P. Bayrock; W.M. Ingledew (Biotechnology Letters, 2002)

Culture of isolated zygotic embryos of Pinus radiata D. Don. Part II: Biochemical changes associated with the conversion of isolated embryos - Xueqin Lin; David W. M. Leung (In Vitro Cellular & Developmental Biology - Plant, 2002)

Culture of isolated zygotic embryos of Pinus radiata D. Don. Part I: Factors influencing in vitro germination and growth of isolated embryos - Xueqin Lin; David W. M. Leung (In Vitro Cellular & Developmental Biology - Plant, 2002)

The balance between supply and demand of water resources and the water-saving potential for agriculture in the Hexi Corridor - Qian-zhao Gao; Hu-lin Du; Rui-ping Zu (Chinese Geographical Science, 2002)

An assessment for sustainable developing capability of integrated agricultural regionalization in China - Xue-gong Xu; Hui-ping Lin; Li-sheng Hou; Xin Yao (Chinese Geographical Science, 2002)

Thoughts on constructing the demonstrating areas of the ecological rebuilding and economic sustainable development in Hexi Region - Chuang-lin Fang; Jin-chuan Huang; Yan-sui Liu (Chinese Geographical Science, 2002)

Structure and development of epiphylly in knox -transgenic tobacco - Jinxing Lin; Kai Mller (Planta, 2002)

Screening of arbuscular mycorrhizal fungi for the revegetation of eroded red soils in subtropical China - Tiehang Wu; Wenying Hao; Xiangui Lin; Yaqin Shi (Plant and Soil, 2002)

Assessment of Treatment Alternatives for Laboratory COD Wastewater: a Practical Comparison with Emphasis on Cost and Performance - Shing Tet Leong; S. Muttamara; Preecha Laortanakul; Hung-Ta Lin (Environmental Monitoring and Assessment, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Modulation of calcium balance in tilapia larvae ( Oreochromis mossambicus ) acclimated to low-calcium environments - Chou M.-Y.; Lu F.-I.; Lin H.-C.; Hwang P.-P.; Yang C.-H. (Journal of Comparative Physiology B, 2002)

Characteristics of micrometeorology in the surface layer in the Tibetan Plateau - Liu Huizhi; Zhang Hongsheng; Bian Lin’gen; Chen Jiayi; Zhou Mingyu; Xu Xiangde; Li Shiming; Zhao Yijun (Advances in Atmospheric Sciences, 2002)

Elevated atmospheric CO 2 alters wood production, wood quality and wood strength of Scots pine ( Pinus sylvestris L) after three years of enrichment - R. Ceulemans; M. E. Jach; R. Van De Velde; J. X. Lin; M. Stevens (Global Change Biology, 2002)
Scots pine ( Pinus sylvestris L.) trees were grown in open top chambers for three years under ambient and elevated CO 2 concentrations. The trees were aged 3 y at the beginning of the CO 2 exposure, and the effects of the treatment on total stem volume, stem wood biomass, wood quality and wood anatomy were examined at the end of the exposure. The elevated CO 2 treatment lead to a 49% and 38% increase in stem biomass and stem wood volume, respectively. However, no significant effects of the elevated CO 2 treatment on wood density were observed, neither when green wood density was estimated from stem biomass and stem volume, nor when oven‐dry wood density was measured on small wood samples. Under elevated CO 2 significantly wider growth rings were observed. The effect of elevated CO 2 on growth ring width was primarily the result of an increase in earlywood width. Wood compression strength decreased under elevated CO 2 conditions, which could be explained by significantly larger tracheids and the increased earlywood band, that has thinner walls and larger cavities. A significant decrease of the number of resin canals in the third growth ring was observed under the elevated treatment; this might indicate that trees produced and contained less resin, which has implications for disease and pest resistance. So, although wood volume yield in Scots pine increased significantly with elevated CO 2 after three years of treatment, wood density remained unchanged, while wood strength decreased. Whilst wood volume and stem biomass production may increase in this major boreal forest tree species, wood quality and resin production might decrease under future elevated CO 2 conditions.

Reactivation of morphine conditioned place preference by drug priming: role of environmental cues and sensitization - Lin Lu; Nan-Jie Xu; Xin Ge; Wen Yue; Wen-Juan Su; Gang Pei; Lan Ma (Psychopharmacology, 2002)

Comparison of Bidirectional Cephalexin Transport Across MDCK and Caco-2 Cell Monolayers: Interactions with Peptide Transporters - Wendy S. Putnam; Lin Pan; Ken Tsutsui; Lori Takahashi; Leslie Z. Benet (Pharmaceutical Research, 2002)

Validity of in Vitro Tests on Aqueous Spray Pumps as Surrogates for Nasal Deposition - Julie D. Suman; Beth L. Laube; Ta-chun Lin; Guillaume Brouet; Richard Dalby (Pharmaceutical Research, 2002)

Stopped-flow kinetic study of the peroxidase reactions of mangano-microperoxidase-8 - Hui-Chun Yeh; Chia-Huei Yu; Jinn-Shyan Wang; Suei-Tein Chen; Oliver Y. Su; Wann-Yin Lin (JBIC Journal of Biological Inorganic Chemistry, 2002)

Genetic variations in the cholesteryl ester transfer protein gene and high density lipoprotein cholesterol levels in Taiwanese Chinese - Lung-An Hsu; Yu-Lin Ko; Kuang-Hung Hsu; Yu-Hsien Ko; Ying-Shiung Lee (Human Genetics, 2002)

High incidence of JC viruria in JC-seropositive older individuals - Han Chang; Meilin Wang; Rong-Tai Tsai; Hui-Sheng Lin; Jin-Shue Huan; Wen-Chuang Wang; Deching Chang (Journal of NeuroVirology, 2002)

Evolutionary and taxonomic implications of conserved structural motifs between picornaviruses and insect picorna-like viruses - L. Liljas; J. Tate; T. Lin; P. Christian; J. E. Johnson (Archives of Virology, 2002)

Structural Model of the Muscle Spindle - Chou-Ching K. Lin; Patrick E. Crago (Annals of Biomedical Engineering, 2002)

Neural and Mechanical Contributions to the Stretch Reflex: A Model Synthesis - Chou-Ching K. Lin; Patrick E. Crago (Annals of Biomedical Engineering, 2002)